2007
DOI: 10.1021/es0628598
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Glomalin-Related Soil Protein and Sequestered Toxic Metals into Watersheds

Abstract: We hypothesized that glomalin-related soil proteins (GRSP) are eroded in sufficient quantities to influence metal loading into watersheds. We tested correlations among GRSP, Glomeromycota fungi, and metals (cadmium, iron, lead, and manganese) in proteins extracted from embankment soils at seven locations along an urban/coastal watershed. Immunoreactive (IRSP) and easily extractable (EE-IRSP) glomalin ranged from 0.007 to 2.9 mg g(-1) and from 0.006 to 0.63 mg g(-1) of soils, respectively. Glomalin-bound metals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(20 citation statements)
references
References 21 publications
1
18
0
1
Order By: Relevance
“…At Site 1, it was highly variable (with an average of 0.22 ± 0.22); while at Site 2, it was 0.54 ± 0.14 and at Site 3, it was 0.56 ± 0.24 mg of EEGS/g. These valued are in accordance to these reported by Chern et al [52], which ranged from 0.007 to 2.9 mg/g soil.…”
Section: Easily Extracted Glomalin From the Slag (Eegs)supporting
confidence: 93%
See 2 more Smart Citations
“…At Site 1, it was highly variable (with an average of 0.22 ± 0.22); while at Site 2, it was 0.54 ± 0.14 and at Site 3, it was 0.56 ± 0.24 mg of EEGS/g. These valued are in accordance to these reported by Chern et al [52], which ranged from 0.007 to 2.9 mg/g soil.…”
Section: Easily Extracted Glomalin From the Slag (Eegs)supporting
confidence: 93%
“…These authors reported that glomalin extracted from two polluted soils (containing between 0.03 and 0.20 mg Cd/g soil determined by DTPA-available Cd) bound between 0.020 and 0.080 mg Cd/g of glomalin. Higher values of metal sequestration were observed by Chern et al [52]. They reported between 0 and 0.34 mg Cd/g protein in sediments containing from 18 mg Cd/g sediment, when the permissible limits are between 8.9 and 9.3 mg Cd/L of sediment.…”
Section: Content In Glomalin Extracted From Slug (Cd-ges) and Frommentioning
confidence: 70%
See 1 more Smart Citation
“…The secreted biomolecules as a result of mycorrhizal symbiosis assist host plants in their growth and strengthen their immune system. Biomolecule produced by fungal hyphae such as glomalin helps host plants to reduce the level of toxicity in soil by converting it into organic form and making it more bioavailable (Sanon et al 2006;Chern et al 2007). …”
Section: Fig 4 Mycorrhizal Dependency (Md) Of G Arborea Seedlingsmentioning
confidence: 99%
“…Elevated levels of Pb in surface waters may be originated from deposits of atmospheric dust, industrial wastewater, urban runoff, and mine tailings (Chern et al 2007). Removal of Pb from the polluted waters and wastewaters is, therefore, important in terms of protection of the public and environmental health.…”
Section: Introductionmentioning
confidence: 99%